The Identity of Christian Pedagogy and the Christian Educator in Light of the Teachings of John Paul II - Olbrycht, Katarzyna (Paedagogia Christiana, 2024)
The problematic and dynamic contemporary socio-cultural situation, and changes in perceptions of Christian culture, require a thorough consideration of the identity of Christian pedagogy, its specificity, and its most important functions. The author assumes that the texts of John Paul II, whose pontificate fell during another difficult time for the world and the Church, can be an important inspiration. During this time many groups turned to him, as one of the most widely recognised authorities, for guidance and help. The analysis uses two concepts of identity: the psychosocial and Charles Taylor’s concept of the moral horizon. Christian pedagogy is a sub-discipline of pedagogy as a science but also concerns Christian pedagogies (pedagogical actions and their programmes) and pre-scientific reflection on this subject. In the author’s opinion, when analysing the identity of this field today, it is necessary to focus not only on its subject – Christian education – but on its specificity as a science, a humanistic-social science, and a science related to Christianity and practised by Christian researchers. Such a perspective appears relatively less frequently in reflections on Christian pedagogy, and it seems to comprehend the important potential and duties of Christian pedagogy, which clearly stem from the teachings of John Paul II. Based on this assumption, his texts (statements, letters, documents) are analysed.